Masa Depan Budaya Hukum Keluarga di Indonesia - Suminah, Vivi; Sukti, Surya (AL-MASHALIH (Journal of Islamic Law), 2025)
Indonesia is a country with the largest Muslim population in the world, but on the other hand, Indonesia is also a country with a diverse indigenous community. So the existence of these two aspects creates a diversity of laws that apply to society. In Indonesia itself, family law has a very important role, it is an integral part of regulating the family life of Indonesian society with diverse cultures, religions, and traditions. Family law in Indonesia faces major challenges to remain relevant and fair. The writing method used by the author in making this paper is library research through several literatures such as books, articles, journals, library searches, and internet site searches. The results of this discussion include. The development of Islamic family law culture in Indonesia is a debate between conservatives who maintain the old legal discourse and modernists who offer laws that are in accordance with the demands of the times. In the Enforcement of Family Law in Indonesia, there are also challenges. One of them is the rampant practice of underage marriage which is widely practiced in Indonesian society, this is due to the very large influence of customs and religious factors that exist in the requirements. In realizing the values ​​of justice, society plays a role in instilling its values ​​through legal awareness in the family, as well as encouragement that is carried out such as caring about gender equality and justice in the household. The role of the government is also very large in ensuring that the policies that are made can be appropriate and effective.